Modeling Information Complex Processing with MMS-Kalman Filter - Kluga, A.; Kluga, J. (Elektronika ir Elektrotechnika, 2007)
Comparison of tow algorithms for mobile object place location with satellite systems is shown in this work. First is the minimum mean-square (MMS) recursive algorithm, which is used for place rough determination and random error filtering (MMS-MMS algorithm). Second is MMS-Kalman filtering algorithm. Estimation of algorithms was obtained by modeling mobile object place location with satellite systems in various dynamic and noise signal situations. Is show, that in case if navigation system have not INS sensors GPS information can be filtered with MMS-MMS algorithm, but if GPS and INS sensors are used MMS-Kalman algorithm can be used. Ill. 6, bibl. 3 (in English, summaries in English, Russian and Lithuanian).